Mais que sont devenus les poissons du delta du Danube ? Les économies morales de la dégradation de la pêche dans une réserve de biosphère - Veronica Mitroi; Jean-Paul Billaud (Développement Durable et Territoires)
The establishment of protected areas in wetlands all over the world is often accompanied by coercive measures for local fisheries, mainly inspired by the model of fishing quotas. Unsuited to the specific small scale fisheries, quota policies consider the degradation of fisheries primarily as a result of overfishing, a failure of the institutional systems that do not succeed to regulate access to the resource. Based on an ethnographic study of fishing rights evolution in the Danube Delta Biosphere Reserve, this article presents the degradation of fish resources as a form of “moral economy”, defining new forms of interaction between actors, resources and environments in order to address environmental uncertainties. We show how the “degradation” of the fishery is the expression of a moral economy, both in the formulation of fishing rights policy and at the level of local practices.